2003
DOI: 10.1182/blood-2002-06-1774
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor inhibits spontaneous cytochrome c release and mitochondria-dependent apoptosis of myelodysplastic syndrome hematopoietic progenitors

Abstract: Low-risk myelodysplastic syndromes (MDS), including refractory anemia and sideroblastic anemia, are characterized by increased apoptotic death of erythroid progenitors. The signaling pathways that elicit this pathologic cell death in MDS have, however, remained unclear. Treatment with erythropoietin in combination with granulocyte colony-stimulating factor (G-CSF) may synergistically improve the anemia in patients with MDS, with a concomitant decrease in the number of apoptotic bone marrow precursors. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
101
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 44 publications
8
101
0
3
Order By: Relevance
“…Similarly, caspase-3 is clearly much more activated in myelodysplastic precursors as compared to their normal counterparts (Bouscary et al, 2000;Claessens et al, 2002;Matthes et al, 2002). Cytochrome c-mediated activation of caspase-9 and downstream caspase-3 was further suggested by the protective effects of cell permeant peptide inhibitors (Tehranchi et al, 2003).…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, caspase-3 is clearly much more activated in myelodysplastic precursors as compared to their normal counterparts (Bouscary et al, 2000;Claessens et al, 2002;Matthes et al, 2002). Cytochrome c-mediated activation of caspase-9 and downstream caspase-3 was further suggested by the protective effects of cell permeant peptide inhibitors (Tehranchi et al, 2003).…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 96%
“…At early stages of acquired myelodysplastic syndromes, exacerbation of the physiological pathway to caspase activation in erythroid cells, even in the presence of elevated Epo concentrations, is responsible for a high rate of apoptosis, ineffective erythropoiesis and increased phagocytosis (Raza et al, 1995;Bouscary et al, 1997;Hellstrom-Lindberg et al, 2001;Shetty et al, 2002;Tehranchi et al, 2003;Testa, 2004). Several observations argue for a role of the Fas-L/Fas pathway in this pathogenic event.…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] We have earlier shown that G-CSF decreases cytochrome c release from mitochondria to cytosol, thereby reducing caspase activation and premature death of cultured MDS erythroblasts. 22,23 However, the precise mode of the antiapoptotic action of G-CSF is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…It also promotes erythroid colony growth and differentiation of stem cells from RARS patients (Schmidt-Mende et al, 2001;Molineau 2011).There is evidence that G-CSF changes the survival abilities of the mobilized CD34+ cells and it was found that peripheral blood stem cell mobilization with G-CSF results in a significant reduction in the number of apoptotic CD34+ cells in comparison with a more apoptotic CD34+ cells collected form an unstimulated mobilization (Philpott et al, 1997). Additionally it has been shown by in vitro experiments that G-CSF blocks spontaneous cytochrome c release and mitochondria-dependent apoptosis in hematopoietic progenitor cells of RARS patients and improves erythropoiesis in MDS (Tehranchi et al, 2003;Sung 2007;Molineau 2011).…”
Section: Combination Of Granulocyte Colony-stimulating Factor and Erymentioning
confidence: 99%